2008
DOI: 10.1128/aem.02240-07
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Dynamics of the Toxic Bloom-Forming Cyanobacterium Microcystis aeruginosa and Its Cyanophages in Freshwater

Abstract: The abundance of potentially Microcystis aeruginosa-infectious cyanophages in freshwater was studied using g91 real-time PCR. A clear increase in cyanophage abundance was observed when M. aeruginosa numbers declined, showing that these factors were significantly negatively correlated. Furthermore, our data suggested that cyanophage dynamics may also affect shifts in microcystin-producing and non-microcystin-producing populations.The major bloom-forming cyanobacterial species Microcystis aeruginosa forms noxiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
77
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 35 publications
4
77
0
Order By: Relevance
“…Cell numbers of Microcystis detected by the qPCR analysis were found to be 1-30 times higher than those by microscopic examination, which is consistent with results of several previous studies (Vaitomaa et al 2003;Hotto et al 2007;Yoshida et al 2008). Lower values of cell abundance examined by the microscopic counting method, especially for Microcystis and cyanobacteria that occur in late winter and early spring having low numbers, may result from the low detection limit, colonial decomposition, and cell loss during the longer fixation procedure by the microscopic counting approach (Hotto et al 2007).…”
Section: Dynamics Of Cyanobacteria and Microcystissupporting
confidence: 81%
See 1 more Smart Citation
“…Cell numbers of Microcystis detected by the qPCR analysis were found to be 1-30 times higher than those by microscopic examination, which is consistent with results of several previous studies (Vaitomaa et al 2003;Hotto et al 2007;Yoshida et al 2008). Lower values of cell abundance examined by the microscopic counting method, especially for Microcystis and cyanobacteria that occur in late winter and early spring having low numbers, may result from the low detection limit, colonial decomposition, and cell loss during the longer fixation procedure by the microscopic counting approach (Hotto et al 2007).…”
Section: Dynamics Of Cyanobacteria and Microcystissupporting
confidence: 81%
“…It is generally known that cyanobacterial blooms, dominated by either Microcystis or Planktothrix, consist of both toxic and nontoxic populations (Kurmayer et al 2002(Kurmayer et al , 2004Yoshida et al 2008). Several recent studies using qPCR or competitive PCR to amplify fragments of the mcy gene involved in MC production have revealed that proportions of mcy-containing Microcystis were relatively low, i.e., 1-38% for mcyB subpopulations in Lake Wannsee, Germany, 0.5-35% for mcyA subpopulations in Lake Mikata, Japan, 0-37% for mcyD subpopulations in Lake Oneida, USA, and 0-48% for mcyD subpopulations in Lake Erie, respectively (Kurmayer and Kutzenberger 2003;Yoshida et al 2007;Hotto et al 2008;Rinta-Kanto et al 2009).…”
Section: Dynamics Of Cyanobacteria and Microcystismentioning
confidence: 99%
“…In accordance with KtW, a number of studies in marine and freshwater environments found that virus and host communities of either specific populations or entire assemblages are linked (26,37,33,51,69,96,98,107,108,112), and there is evidence suggesting similarly coupled prokaryotic and viral communities in a soda lake (80). The details vary, however.…”
Section: Observational Studiesmentioning
confidence: 91%
“…In agreement with KtW, those authors' results show that viruses were closely linked to the developments in the microbial community. Also, Wang and Chen (98) investigated the population dynamics of cyanovirus communities, and Yoshida et al (112) studied the dynamics of viruses infecting the toxic bloom-forming cyanobacterium Microcystis aeruginosa. Both studies found that changes in the virus communities were related to changes in the host communities, supporting KtW.…”
Section: Observational Studiesmentioning
confidence: 99%
“…Cyanobacterial viruses, termed "cyanophages," are also abundant in both marine and freshwater ecosystems and play an important role in regulating the cyanobacteria biomass and community structure, controlling the cyanobacteria bloom, mediating the horizontal gene transfer between cyanobacterial hosts and maintaining the extensive diversity of microbial communities (Lindell et al, 2004;Sullivan et al, 2005;Yoshida et al, 2008;Gao et al, 2009;Zhang and Gui, 2012;Li et al, 2013;Ou et al, 2013;Zhang, 2014). As a preface to gain insight into the biological properties of cyanophages and their interactions with cyanobacterial hosts at the molecular level, it is necessary to obtain their complete genome sequences.…”
mentioning
confidence: 99%